Sensitive Detection of Rhodamine B Using Surface Enhanced Raman Spectroscopy with a BiFeO3 based Substrate - Mayora, Diva Cassia; Triyono, Djoko; Shiddiq, Muhandis; Rafsanjani, Rifqi Almusawi; Alaih, Akhmad Futukhillah Fataba (Journal of Engineering and Technological Sciences, 2025)
Surface-Enhanced Raman Spectroscopy (SERS) is a highly effective technique for detecting trace amounts of molecular species. However, the widespread use of conventional noble metal substrates is limited by high fabrication costs and scalability issues. Perovskite materials have recently emerged as promising alternatives, though many are lead-based and pose environmental risks. In this study, we present a lead-free bismuth ferrite (BiFeO₃) perovskite synthesized via the sol–gel method as a novel SERS substrate for the detection of Rhodamine B, a toxic dye commonly used illicitly in food products. Comprehensive characterization using X-ray Diffraction (XRD), X-ray Fluorescence (XRF), and UV-Visible Diffuse Reflectance Spectroscopy confirmed the successful formation of a single-phase rhombohedral structure with a direct bandgap of 2.1 eV, indicating strong visible-light absorption. The BiFeO₃ substrate demonstrated effective SERS performance, facilitating a detection of Rhodamine B at concentrations as low as 10 ppm. These results highlight the potential of lead-free BiFeO₃ perovskites as practical and environmentally friendly alternatives to noble metals for SERS-based detection of hazardous dyes and other environmental contaminants.